Experimental study of detachment density threshold in L-mode plasmas on EAST. (7th May 2020) - Meng, L Y; Liu, J B; Xu, J C; Wang, L; Xu, G S; Guo, H Y; Liu, X J; Si, H; Wang, H Q; Ge, W D; Lan, H; Chen, L; et al.
Abstract: One of the critical challenges for long pulse operation of ITER and future fusion reactors is the excessively high heat and particle fluxes on the divertor targets. The divertor detachment offers an effective way for the control of steady state heat flux and erosion at the divertor target. Dedicated experiments have been systematically performed for both H-mode and L-mode plasmas on EAST with ITER-like W divertor in the last two years to further advance detachment physics understanding. The detachment is identified by the rollover of divertor peak particle flux near the strike point during the density ramping up, which correlates with the reduction of electron temperature down to 5 eV, the increase of D δ / D α ratio and radiated power. It has been demonstrated that the more closed divertor has a lower density threshold at the onset of detachment on EAST. Furthermore, the detachment density threshold will be reduced when the strike point moves towards the divertor corner. The onset of detachment exhibits a strong asymmetry between inner and outer targets, with the inner target accessing detachment at lower density due to the lower electron temperature, as expected. The effects of the heating power and plasma current on the detachment onset were also investigated. The experimental results show that the density at detachment onset is lower in L-mode relative to H-mode, and increases with the heating power. The detachment density threshold normalized to the Greenwald density limit is lower at a high plasma current.